"Seeing the Other Side": Empowering the Voices of Latinx Middle School Students. Issue 2 (4th May 2021) - Stickl Haugen, Jaimie; Waalkes, Phillip L.; Neverve, Candice
ABSTRACT: School counselors are in a unique position to recognize the strengths of Latinx students and help empower their voices to be heard. Given the divisive sociopolitical landscape in the United States, there is a need to provide space for Latinx youth to share their experiences in contemporary society. The current study used photovoice to elicit Latinx middle school students' experiences through photography and encourage students to engage in critical dialogue and social action. Five themes and four subthemes emerged providing valuable insight into Latinx youth experiences in the United States. Overarching themes included connections and support, challenges, desire for equity, cultural identity, and value of education. Findings have valuable implications for school counselors who work with Latinx students.